PREDIKSI TINGKAT BAHAYA EROSI MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS (SIG) DI DAERAH TANGKAPAN AIR DANAU WISATA BANDAR KAYANGAN - Suyanti, Eva; Hadinoto, Hadinoto; Ikhwan, Muhammad (Wahana Forestra: Jurnal Kehutanan, 2017)
This study aims to determine the level of erosion hazard through erosion prediction by USLE method and Geographic Information System (GIS) at Water Catchment Area (WCA) Danau Wisata Bandar Kayangan. This research was conducted at WCA Danau Wisata Bandar Kayangan, Limbungan Village, District Rumbai, Pekanbaru. The research data was collected by survey method. Secondary data collection includes a slope digital map, land cover map, rainfall data, and soil type map of WCA Danau Wisata Bandar Kayangan. While the primary data is done by field checking to know land use pattern and soil type around WCA Danau Wisata Bandar Kayangan. The result shows that the erosivity index (R) is 108. The soil erodibility index (K) in Podsolik Merah Kuning (PMK) is 0.166. Slope length index (LS) on slope <8% flatland (20), 8 -15% ramps (15), 16 - 25% slightly steep (10). Crop management and soil conservation (CP) index covers settlement (1), Bush / 0.01), plantation (0,02), and lake (0,01). The result of overlay of rainfall maps, soil type, slope class, and crop management and soil conservation obtained 46 land units at WCA Danau Wisata Bandar Kayangan. The highest Erosion Hazard Index (EHI) is found on land unit 45 of 358 on residential land cover. The largest potential erosion on land unit 44 with soil loss is 41,189.45 ton / ha / yr. Level of EHI in WCA Area of Danau Wisata Bandar Kayangan includes Class EHI1: Very Light area of 32,627 ha; EHI Class 2: Lightweight of 59.86 ha; Class EHI 3: Medium area of 247.52 ha; Class EHI 4: Weight of 977,127 ha, Class EHI 5: Very Weight of 4,549.43 ha.